Human Rabies: Optimization of Prevention and Paths Towards the Cure - Conceição, Paulo (2021)
Introduction: Rabies is one of the oldest and deadliest infectious diseases known by human beings and is commonly transmitted by animal bites. Dogs have a major role in the transmission of the virus. Rabies has no approved curative therapy, and its prevention, even though it is highly effective, it is complex, expensive and challenging in terms of accessibility, particularly regarding immunoglobulin. This review aims to provide a practical approach to cost-effective prevention as well as the future perspectives regarding the development of an effective and secure cure.Material and Methods: This review article was based on a search in PubMed using the following MeSH terms: rabies, preexposure and postexposure prophylaxis, rabies immune globulin, treatment, Milwaukee Protocol.Results: Concerning rabies infection, it’s important to apply the prevention protocols effectively as early as possible due the unpredictable time window between infection and the appearance of symptoms. The literature shows that is possible to reduce the vaccination dosage and maintain the efficiency of the immunization, and booster vaccination is only required in specific risk groups/populations.Discussion: The current philosophy of cost-effective prevention which consists of canine vaccination, restriction of vaccine overdosage used in humans and the appropriate use of rabies immunoglobulin – could make the prevention of the disease accessible for those countries that need it the most. There are several therapies in development but they’re all in early stages of development.Conclusion: The development of new and more effective therapeutic and prophylactic approaches is a goal not yet achieved and relies on a better understanding of the disease pathophysiology.